MEDIA ATLAS ANATOMI DAUN TANAMAN HIAS MONOKOTIL YANG DIPENGARUHI TRANSPIRASI - Febriyani, Pangesti Ayu Wandari; Daningsih, Entin; Mardiyyaningsih, Asriah Nurdini (Universitas Tanjungpura, 2023)
Submaterial structure and function of plant tissue is a one of thedifficult materials for student to learn. Media can help to understandeasier for student and therefore is need. The studied was to make anatlas media and to know the validity of the atlas media about leafanatomy and physiology on the plants structure and functionsubmaterial in class XI. The method of these research is descriptivequantitative. Atlas media was made with three stages including thepre-production, production, and post-production. The instrumentsvalidation used were questionnaire instruments and questionnairevalidation media which consisted of four aspects such us presentation,language, and usage with 21 indicators. The instrument validationquestionnaire was validated by two instrument experts, while themedia atlas was validated by two Biology Education lecturers at theTanjungpura University (FKIP Untan) and three biology teachers classXI using a Likert scale. The validation results were analyzed accordingto Laswhe. The results of the instrument validation show that theinstrument was suitable for use, while the results of the mediavalidation showed that the presentation aspect (0.85) and contentaspects (0.94) were not yet valid because has not reached the minimumCVR by Lawshe (0.99). The validation results of the atlas media havenot reached the minimum CVI; the value of validation atlas media wasabout 0.92 so it needs improvement before being used in learning.